Основні етапи технології розробки тримірних моделей архітектурних об'єктів для мультимедійних видань - Дейнека, Д. В. (ХНУРЕ, 2022)
Architectural forms of buildings are first born in the imagination of the architect as harmonious and beautiful three-dimensional images. The history of the development of architecture proves that the authors of buildings of all historical periods perfectly possessed the means of 3D modeling, perfectly transferring monumental ideas on the plane of drawings. It is simply impossible to erect a structure without understanding and masterful operation of such elements of three-dimensional design as shape and volume, planes and sections. Creating 3D architectural models, even at the primitive level, requires knowledge of the basic properties of materials and a full understanding of construction technologies.
Keywords: модель архітектурних об'єктів; мультимедійне видання